DEVELOPMENT OF THE “SI MENTAL BK” APPLICATION AS A MEDIUM FOR EXPRESSING STUDENTS' MENTAL HEALTH AT THE UPT SPF SMP NEGERI 9 MAKASSAR - Febriana Angraeni; Abdullah Pandang; Sahril Buchori (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to develop the